2016
DOI: 10.1080/01480545.2016.1212366
|View full text |Cite
|
Sign up to set email alerts
|

Fetopathies associated with exposure to angiotensin converting enzyme inhibitor fromTropaeolum majusL.

Abstract: The prevalence of the use of herbal medicines is on the rise across the world, especially amongst pregnant women. A fact that draws attention is that many species commonly used by pregnant women, including the Tropaeolum majus L. (Tropaeolaceae), also present inhibitory activity on the angiotensin-converting enzyme (ACE). Herein, we have investigated the effects of T. majus extract (HETM) on fetal development, evaluating its relationship with possible ACE inhibitory activity. Pregnant Wistar rats were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…It has been shown to have inhibitory action on the angiotensin-converting enzyme, and cause growth restriction and renal damage after 20 days of gestation in rats. 14 An ethobotany survey in Eastern Ivory Coast found that 90% of pregnant women used medicinal plants during pregnancy. 15 Similarly, 80% of pregnant women in Mali used medicinal plants during pregnancy, principally for treatment of malaria, urinary tract infections and reduction of oedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to have inhibitory action on the angiotensin-converting enzyme, and cause growth restriction and renal damage after 20 days of gestation in rats. 14 An ethobotany survey in Eastern Ivory Coast found that 90% of pregnant women used medicinal plants during pregnancy. 15 Similarly, 80% of pregnant women in Mali used medicinal plants during pregnancy, principally for treatment of malaria, urinary tract infections and reduction of oedema.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have inhibitory action on the angiotensin-converting enzyme, and cause growth restriction and renal damage after 20 days of gestation in rats. 14…”
Section: Discussionmentioning
confidence: 99%
“…The renin–angiotensin system augments ureteric bud branching, and maternal use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers is associated with renal agenesis and anomalies [131]. Other medications, including glucocorticoids, mycophenolate mofetil, antiepileptic drugs, and cyclophosphamide may be associated with renal anomalies [132136].…”
Section: Adverse Fetal Environment Effects On Renal Developmentmentioning
confidence: 99%
“…Tropaeolum majus L. es una planta nativa de los andes de Sudamérica (Perú, Colombia y Brasil) que actualmente se encuentra ampliamente distribuida en todo el mundo [11,12] . Sus grandes flores de color naranja, amarillo o rojo; que florecen desde la primavera hasta el otoño, se utilizan en la alimentación y la medicina popular [13] .…”
Section: Introductionunclassified